2014
DOI: 10.2147/cia.s64723
|View full text |Cite
|
Sign up to set email alerts
|

Case management for dementia in primary health care: a systematic mixed studies review based on the diffusion of innovation model

Abstract: BackgroundThe purpose of this study was to examine factors associated with the implementation of case management (CM) interventions in primary health care (PHC) and to develop strategies to enhance its adoption by PHC practices.MethodsThis study was designed as a systematic mixed studies review (including quantitative and qualitative studies) with synthesis based on the diffusion of innovation model. A literature search was performed using MEDLINE, PsycInfo, EMBASE, and the Cochrane Database (1995 to August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 45 publications
(169 reference statements)
3
71
0
2
Order By: Relevance
“…A number of systematic reviews have been reported of studies assessing the impact of case management on older people with dementia. [183][184][185][186][187][188][189] In general, studies have provided conflicting information about the potential benefits and duration of effect of case management for people with dementia. A recent Cochrane review of case management for PLWD found that the case management group was significantly less likely to be institutionalised at 6 and 12 months than those not receiving case management, although the longer-term effects were uncertain.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…A number of systematic reviews have been reported of studies assessing the impact of case management on older people with dementia. [183][184][185][186][187][188][189] In general, studies have provided conflicting information about the potential benefits and duration of effect of case management for people with dementia. A recent Cochrane review of case management for PLWD found that the case management group was significantly less likely to be institutionalised at 6 and 12 months than those not receiving case management, although the longer-term effects were uncertain.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…The reviewers described high-intensity case management as (1) a caseload of fewer than 50 patients per fulltime equivalence, (2) regular meetings with the informal caregiver and the patient with at least 50% of these meetings being face to face, (3) education on health conditions, (4) close contact with family physicians, 9,32 and (5) proactive and timely follow-up 9,33 and following up with patients during hospitalizations and short-term institutionalizations. 9,34 In our study, both case management groups exceed this case load recommendation and it is unclear how they rate on the other factors. The average caseloads being over the recommendation of the review could be a possible reason for there being little difference among all groups.…”
Section: Comparison With Literaturementioning
confidence: 53%
“…It is possible that participants in our study had more behavior problems, as total NPI mean baseline scores were higher in our population compared with the patient population in Callahan et al 31 A review that included both qualitative and quantitative studies looked at facilitators and barriers to successful case management implementation in the primary health care setting. 9 Results indicated that high-intensity case management was necessary and sufficient to produce positive clinical outcomes for patients and to optimize service use. The reviewers described high-intensity case management as (1) a caseload of fewer than 50 patients per fulltime equivalence, (2) regular meetings with the informal caregiver and the patient with at least 50% of these meetings being face to face, (3) education on health conditions, (4) close contact with family physicians, 9,32 and (5) proactive and timely follow-up 9,33 and following up with patients during hospitalizations and short-term institutionalizations.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][20][21][22] Our previous studies demonstrated that the effectiveness of CM depends on a small caseload, regular and proactive follow-up, and transparent communication among health care professionals. 110,111 Limitations As in any systematic review, we may have missed studies that we should have included. It is unlikely, however, that we missed large studies, as the literature search was comprehensive and included publications in 3 languages (English, French, and Russian).…”
Section: Discussionmentioning
confidence: 99%